INNOVATIVE METHODS FOR ENHANCING LANGUAGE LEARNING MOTIVATION AMONG UNIVERSITY STUDENTS (KONFERENSIYA, 2025)
Motivation plays a crucial role in effective foreign language acquisition, particularlyin higher education, where students encounter academic demands, digital diversions,and varying learning styles. This research explores creative teaching approaches thatboost language learning motivation in university students. The study outlines fiveprimary motivational strategies: gamification, mobile-assisted language learning,flipped classroom, AI-supported task-based learning, and project-based learning.Results show that interactive, technology-enhanced, and autonomy-focused methodssignificantly increase learners’ engagement, intrinsic motivation, and persistence. Thefindings highlight the importance of integrating modern educational technologieswith communicative, student-centered teaching approaches